(untitled) (JURNAL ADMINISTRASI PUBLIK, 2015)
In any case, however we can not be shifted from the fact that the face of life as it is today, partly determined by existing human resources. For, as we already know, most of the future is determined by human actions. What we do today, significantly affects the face tomorrow. Feels or does not present the progress of science and technology (Science and Technology) has been so rapid. Communication of information has brought progress and changes in all fields, especially the progress of the quality of Human Resources to create a skilled, competent, skilled cultured and virtuous in the face of opportunities and challenges in the future. Therefore, the research is the Regional Government Strategy in Improving Quality of Human Resources in the West District of Manokwari regency Manokwari, West Papua Province. This study uses qualitative research method using data analysis techniques SWOT. Analysis of internal Fator produce factors strengths and weaknesses. Strength (Strengths) that repon The High Society, Special Autonomy Fund The Big and The Big Local Revenue. Weaknesses (Weakness) that low levels of education, lack of guidance and Labor Productivity Development, Lack of Infrastructures, lack of experts and lack of attention from the Government. External factors result in opportunities adann threat factor. Opportunity Factors (Opportunities), namely the Advancement of Technology and Natural Resource Rich. Threat factor (Threatments) ie Mindset That Less Open, Intervention Of Public Affairs and Poverty Level. Based on the SWOT analysis, set out four strategies, namely: mengupayahkan expansion and equity of education and productivity enhancement and development of society, improvement of public services with improved quality of personnel and the implementation of balanced development, encourage increased intervention and public awareness, exploritation potential areas based technology. Key words : Strategies of local governments in improving the quality of human resources, SWOT